1999
DOI: 10.1111/j.1600-0838.1999.tb00200.x
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and organ transplantation

Abstract: Life‐saving treatment of disease by organ transplantation has become increasingly important. Annually over 35 000 transplantations of vital organs are carried out world‐wide and the demand for knowledge regarding exercise in daily life for transplant recipients is growing. The present review describes whole‐body and organ reactions to both acute exercise and regular physical training in persons who have undergone heart, lung, liver, kidney, pancreas or bone marrow transplantation. In response to acute exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 126 publications
0
12
0
Order By: Relevance
“…Given the quotation in the introduction [4], which, in essence, states that it is the comradeship of peers, the return to being physically active again and the triumph of coping with adversities in life that give the games their unique flavor, it is no surprise that the apparently reappraised attitude towards the competitive aspects of the games are diminished and partly replaced by other basic needs for participation, such as social and wellbeing factors. This notion is also stressed by [1,5] , who emphasize several advantages of physical training for transplanted athletes, such as improved quality of life rather than mere competition. It is also interesting to note the relatively high educational level of participants at the WTG (62% university degree) as compared to statistics from other Western countries in relation to educational background and sport participation.…”
Section: Analysis Of the Descriptive And Inferential Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the quotation in the introduction [4], which, in essence, states that it is the comradeship of peers, the return to being physically active again and the triumph of coping with adversities in life that give the games their unique flavor, it is no surprise that the apparently reappraised attitude towards the competitive aspects of the games are diminished and partly replaced by other basic needs for participation, such as social and wellbeing factors. This notion is also stressed by [1,5] , who emphasize several advantages of physical training for transplanted athletes, such as improved quality of life rather than mere competition. It is also interesting to note the relatively high educational level of participants at the WTG (62% university degree) as compared to statistics from other Western countries in relation to educational background and sport participation.…”
Section: Analysis Of the Descriptive And Inferential Resultsmentioning
confidence: 99%
“…Previous research has clearly pointed out several medical and physical benefits for participation in physical activity aimed at this group, such as physical training resulting in improved endurance, strength and capacity in almost all groups of transplant recipients [1]. Other studies generally state that transplant recipients tolerate progressive exercise training well and can achieve levels of functioning similar to, or even higher than, those of the general population [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With properly selected physical activity, patients can obtain results comparable to healthy individuals at a similar age. 19 Although this study shows the benefits of exercise in patients after liver transplant, very few studies have focused on the assessment of physical activity in patients after liver transplant, and a lack of standardized testing methods makes it difficult and often impossible to compare results with other papers. In summary, in this cross-sectional prospective study, we have shown that female patients remain significantly less physically active than male patients after liver transplant.…”
Section: Discussionmentioning
confidence: 87%
“…96 Blood pressure is also affected in kidney transplant recipients due to denervation of the transplanted kidney, so blood pressure could be higher in these individuals following exercise. 98 To illustrate these cardiovascular issues, researchers employing a prospective research design tested exercise capacity in 16 kidney transplant recipients for 2 years following transplantation. Peak oxygen consumption (VO 2 max) was significantly lower in the transplant recipient group compared to the healthy control group at 1, 4 and 10 months but not at 16, 24 and 48 months.…”
Section: Health Benefits In Kidney Transplant Recipientsmentioning
confidence: 99%